Chapter К списку двувидовых глаголов в русском языке: история пасть - Plungian, Vladimir (Biblioteca di Studi Slavistici, 2017)
The paper is concerned with the history of the Russian verb past' 'fall', which until the mid-19th century used to have biaspectual present forms. The analysis deals both with the historical motivation for this biaspectual behaviour and the factors behind its loss. The most important stage of the process seems to be the gradual disappearance of the primary spatial usages of past': these came to be expressed by a newly created aspectual pair, padat'/upast'. The latter is close to the so-called two-stem perfectivation verbs, which I examined in more detail in my previous work.